The Associations Between Problematic Internet Use, Healthy Lifestyle Behaviors and Health Complaints in Adolescents - Klavina, Aija; Veliks, Viktors; Zusa-Rodke, Anna; Porozovs, Juris; Aniscenko, Aleksandrs; Bebrisa-Fedotova, Luize (Frontiers in Education, 2021)
This study aimed to explore relationship between problematic internet use (PIU), healthy lifestyle behaviors and subjective health complaints. Methods: Participants (396 adolescents, aged 11-18 years) from 34 general education schools across Latvia completed online survey. The PIU was assessed by the Problematic and Risky Internet Use Screening Scale (PRIUSS) collecting data on social impairment, emotional impairment, and risky/impulsive internet use. The subjective health complaints assessed were somatic and psychological symptoms. Healthy lifestyle behaviors assessed were daily physical activities, time spent in using information technologies (IT), eating habits, and duration of sleep. Results: This study found that 31.00 % (n = 124) of the participants scored at risk for PIU. Correlates associated with PIU were subjective health complaints, low physical activity, lack of meals together with family and disturbed sleeping regimes on weekends (P <.001). Stepwise multiple regression analyses showed that 34% of the variance in the PRIUSS scores was explained by psychological health complaints (irritability, depression, and nervousness), screen time use on weekends, physical activity, drinking sweetened soft drinks and unhealthy eating habits. Conclusions: PIU behaviors among adolescents in Latvia are associated with psychological symptoms and unhealthy lifestyle. Further effective measures and interventions are needed to prevent development of psychosomatic health problems.